2023
DOI: 10.1021/acs.joc.2c02719
|View full text |Cite
|
Sign up to set email alerts
|

Ball-Milling-Enabled Zn(OTf)2-Catalyzed Friedel–Crafts Hydroxyalkylation of Imidazo[1,2-a]pyridines and Indoles

Abstract: A facile and efficient synthetic method for the construction of C3-hydroxyalkylated imidazo­[1,2-a]­pyridines and indoles by a Zn­(OTf)2-catalyzed Friedel–Crafts hydroxyalkylation of imidazo­[1,2-a]­pyridines and indoles with carbonyl compounds under mechanochemical conditions is reported. Good product selectivity, shorter reaction time, ambient reaction temperature, tolerance of a wide range of functional groups, broad substrate scope, moderate to good yield of products, and scalability are the salient featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Deng et al demonstrated a Rh­(III)-catalyzed [4 + 2]-annulation of 2-arylbenzo­[ d ]­imidazoles with maleimides to construct cis -dihydrobenzimidazo­[2,1- a ]­isoquinolines . In a continuation of our interest in the synthesis of N -heterocyclic compounds under transition-metal catalysis, herein, we report a ruthenium-catalyzed C–H/N–H annulation of 2-alkenyl/2-arylimidazoles with N- substituted maleimides and 1,4-naphthoquinone to construct a series of imidazo-fused polyheterocyclic frameworks (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…Deng et al demonstrated a Rh­(III)-catalyzed [4 + 2]-annulation of 2-arylbenzo­[ d ]­imidazoles with maleimides to construct cis -dihydrobenzimidazo­[2,1- a ]­isoquinolines . In a continuation of our interest in the synthesis of N -heterocyclic compounds under transition-metal catalysis, herein, we report a ruthenium-catalyzed C–H/N–H annulation of 2-alkenyl/2-arylimidazoles with N- substituted maleimides and 1,4-naphthoquinone to construct a series of imidazo-fused polyheterocyclic frameworks (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…Imidazoheterocycle motifs possess various useful biological and medicinal activities . Particularly, the sulfenylation of imidazo­[1,2- a ]­pyridine derivatives has gained attention in recent years.…”
Section: Introductionmentioning
confidence: 99%